Anticoagulant effects of protein C, protein S, and antithrombin levels on the protein C pathway in young children - Nakagawa, Takashi; Ogiwara, Kenichi; Tonegawa, Hitoshi; Takahashi, Yukihiro; Nishikubo, Toshiya; Nogami, Keiji (International journal of hematology, 2024)
The protein C (PC) pathway involves physiological anticoagulant factors (PC, protein S [PS], and factor V) and performs major anticoagulant functions in adults. Variations in overall PC pathway function due to dynamic changes in PC and PS in early childhood are poorly understood. We aimed to evaluate the contributions of PC pathway function during early childhood by measuring changes in plasma thrombin generation (TG) after administration of the PC activator protac. We evaluated correlations between anticoagulant factors and percentage of protac-induced coagulation inhibition (PiCi%). Before protac addition, TG in newborns ( n = 35), infants ( n = 42), young children ( n = 35), and adults ( n = 20) were 525 ± 74, 720 ± 96, 785 ± 53, and 802 ± 64 mOD/min, and PiCi% were 42.1 ± 9.9, 69.8 ± 11.0, 82.9 ± 4.4, and 86.9 ± 3.4%, respectively. The distribution of PiCi% on the two axes of TG (with or without protac) changed continuously with age and differed from that of warfarin-treated plasma and adult PC- or PS-deficient plasma. PiCi% increased dynamically during infancy and correlated with PS levels in newborns and PC levels in young children. Addition of PC or fresh frozen plasma equivalent to approximately 25% PC to PC-deficient plasma improved PiCi%. This automatic measurement requires only a small sample volume and is useful for analysis of developmental hemostasis.